Opioids in Headache. Issue 1 (January 2014) - Levin, Morris
<x xml:space="preserve">Abstract</x> Opioid analgesics have long been used to treat head pain of various types. This has been increasing to a significant degree over the past 25 years because of a trend for more liberal use of opioids in non‐malignant pain. Opioid treatment for acute headache, as well as prophylactically for refractory chronic headache, is controversial. There are a number of adverse effects associated with acute and chronic opioid treatment. Tolerance, dependence, and addiction are prominent issues. This article attempts to analyze the benefits and disadvantages for opioids in the management of migraine and other headache disorders, relying on known properties of this class of medication as well as clinical data. It will mainly focus on 2 topics: the use of opioid medication for the acute treatment of migraine attacks and continuous prophylactic use for refractory chronic migraine.